IMPLEMENTASI KEBIJAKAN PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM DAERAH STUDI KASUS PADA RSUD TIDAR KOTA MAGELANG - , SUSI GUSTINI ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims to find out about implementation of Badan Layanan Umum Daerah (BLUD) financial management policies, by case study at District General Hospital (RSUD) Tidar Magelang. The policy of BLUD is one of the manifestations of bureaucratic reformation,in a way to agencificate public service. This research attempts to examine how far the determination of financial management pattern of BLUD (PPK-BLUD) is successfully implied, and also to identify factors to influence the successful of the policy implementation. Based on result of the research, it is understood that the implementation of PPK-BLUD at RSUD Tidar is partly successful and partly not. Some successful matters are financial management by BLUD cash, mechanism of procurement of goods and services that is more efficient and flexible, costing system by the executive decision, application of accounting system and financial report by SAK (GAAP). Meanwhile, the unsuccessful matters are the arrangement of plan and budget by RBA and application of remuneration system for the employees. The success of implementation of PPK-BLUD is caused by some factors. First, support from elite politicians in government body of Magelang. This support is a form other than compliance with the policies of the central government, also based on historical factors that Tidar hospitals have become self-financing unit of regional self-finance even a pioneer unit area before the rising of BLUD policy. This demonstrates the Magelang government's commitment to community health services. This support is a form of compliance with the central government policies, also based on the will to improve health services to the Magelang people. However, because of the wide-impact of BLUD implementation, the political support does not reach to the attempts of facilitating to imply the policy. Secondly, communication in either internal and external. Internal communication between manager and the worker of BLUD, communication between the BLUD leaders and the Mayor, and communication with BLUD stakeholders are many factors that determine the effectiveness of implementing various provisions of the PPK-BLUD. Thirdly, the content of the policy itself, in which accommodates interests of relevant parties. Some rules are easily applied, some are difficult due to the lack of technical guidelines of the implementation and contains potential conflicts. Due to the problems above, researchers recommend :1) to the BLUD policy maker to provide technical guidelines RBA arrangement and clear provision about remuneration. 2) to the district government and staff to facilitate the implementation of the provision of PPK-BLUD. 3) to the head of BLUD and staff to build intensive-communication internal and external, and another way to be transparant on financial management.